Let's talk French. (Living language multimedia, 1995)
SUMMARY: facilities learning over 2,200 French words grouped alphabetically and by subject. Speech recognition feature and record/ playback function help the user improve pronounciation. Includes photographs, games, exercises and French-English glossary.